PELUANG DAN TANTANGAN IMPLEMENTASI CORE TAX ADMINISTRATION SYSTEM (CTAS) DALAM MENDORONG TRANSFORMASI LAYANAN PAJAK DI INDONESIA - Rahma Wati; Almanuri Ashofi; Feni Andriani (Equilibrium Journal of Economic and Development Studies, 2025)
The Core Tax Administration System (CTAS), launched in January 2024, marks a major step in Indonesia’s digital tax reform. This study examines its opportunities and challenges in transforming tax services. Using a qualitative approach through literature review and content analysis of secondary data, particularly media reports and public documents, the research finds that CTAS has strong potential to improve efficiency, transparency, and integration of tax administration. However, implementation has been hindered by technical disruptions, uneven infrastructure, limited human resource readiness, and low digital literacy among taxpayers. The accelerated rollout without extensive pilot testing also led to operational issues and declining user trust. To address these obstacles, the study highlights the need for continuous system evaluation, capacity building for tax officials, and comprehensive taxpayer education. Ensuring inclusiveness and reliability will be crucial for CTAS to function not only as a technological innovation but also as a foundation for sustainable tax service transformation.